The Role of Government and External Relations Department of PT INALUM in Building Public Perception of Environmental Programs in Batu Bara Regency - Sandra Vanya; Muhammad Husni Ritonga (Ali Institute of Research and Publication, 2026)
This study aims to analyze the role of the Government and External Relations Department of PT Indonesia Asahan Aluminium (PT INALUM) in shaping public perception of the company’s environmental programs in Batu Bara Regency. The presence of large-scale industrial companies often raises concerns regarding environmental impacts, making corporate communication an important factor in building public understanding and trust. This study employs a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation, and analyzed qualitatively through data organization, categorization, and theme identification. The findings show that the Government and External Relations Department acts as a communication bridge between the company and the community by delivering environmental programs through socialization activities, dialogue forums, and digital media. The department also facilitates two-way communication by accommodating community feedback and conveying it to management. These communication practices contribute to building public understanding and fostering positive perceptions toward environmental programs such as mangrove planting and environmental conservation. However, several challenges were identified, including unequal participation in communication activities, differences in stakeholder interests, and varying levels of public understanding, which may lead to information gaps within the community. Despite these challenges, the communication efforts carried out by the department are generally effective in enhancing public trust and minimizing potential conflict.